1971
DOI: 10.1021/ja00743a016
|View full text |Cite
|
Sign up to set email alerts
|

Directive effects in the monohydroboration of alkynes and enynes

Abstract: Monohydroboration of terminal alkynes such as 1-octyne and phenylacetylene with dicyclohexylborane or thexylborane (2,3-dimethyl-2-butylborane) places the boron nearly exclusively at the terminal position of the triple bond. 2-Methyl-1 -buten-3-yne and 1 -ethynylcyclohexene react similarly with these mono-and dialkylboranes to afford high yields of the corresponding terminal dienylboranes. The direction of addition of dicyclohexylborane or disiamylborane (bis(3-methyl-2-butyl)borane) to unsymmetrically disubst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(18 citation statements)
references
References 1 publication
(1 reference statement)
0
16
0
1
Order By: Relevance
“…Later, they extended their studies to hydroboration of substituted enynes, 2-methyl-1-buten-3-yne, 1-ethynylcyclohexene and 1-hexen-5-yne, with Cy 2 BH or thexylborane (2,3-dimethyl-2butylborane). [17] Monohydroboration of 2-methyl-1-buten-3-yne gave trans-3-methyl-l,3-butadiene-l-d, after the deuterolysis of the intermediate dienylborane. The result showed that BÀ H bond addition takes place exclusively at the terminal carbon of triple bond.…”
Section: Catalyst Free Hydroboration Of Enynesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, they extended their studies to hydroboration of substituted enynes, 2-methyl-1-buten-3-yne, 1-ethynylcyclohexene and 1-hexen-5-yne, with Cy 2 BH or thexylborane (2,3-dimethyl-2butylborane). [17] Monohydroboration of 2-methyl-1-buten-3-yne gave trans-3-methyl-l,3-butadiene-l-d, after the deuterolysis of the intermediate dienylborane. The result showed that BÀ H bond addition takes place exclusively at the terminal carbon of triple bond.…”
Section: Catalyst Free Hydroboration Of Enynesmentioning
confidence: 99%
“…This result showed the directing effect of the boryl moiety in the hydroboration reaction. Later, they extended their studies to hydroboration of substituted enynes, 2‐methyl‐1‐buten‐3‐yne, 1‐ethynylcyclohexene and 1‐hexen‐5‐yne, with Cy 2 BH or thexylborane (2,3‐dimethyl‐2‐butylborane) . Monohydroboration of 2‐methyl‐1‐buten‐3‐yne gave trans ‐3‐methyl‐l,3‐butadiene‐l‐ d , after the deuterolysis of the intermediate dienylborane.…”
Section: Catalyst Free Hydroboration Of Enynesmentioning
confidence: 99%
“…The equivalent reaction with internal alkynes is more controlled, and reasonable yields of the corresponding cis -trialkenylboranes can be obtained (Scheme 15.1 ) [37] . However, unsymmetrical internal alkynes react with only modest regioselectivity [38] . Both steric and electronic factors affect the regioselectivity of monohydroboration ( Figure 15.3 ).…”
Section: Hydroborationmentioning
confidence: 99%
“…Optically active 3a was prepared from (lS,2S)-(+)-dimethyI trans-1,2-cyclobutanedicarboxylate (34), 56.2 (c 20.3, CCl4), 38.2% optically pure, by reduction to the dialdehyde, which then was treated with methylidenetriphenylphosphorane. The water was removed under reduced pressure and the contents of the flask were taken up in ether.…”
Section: Correlation Of (Ls2s)-(+)-trans-l2-cyclobutanedicarboxylicmentioning
confidence: 99%